2017
DOI: 10.3177/jnsv.63.81
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-Like Effect of 1&alpha;-Hydroxyvitamin D<sub>3</sub> on Mice in the Forced Swimming Test

Abstract: SummaryWe examined the effect of 1a-hydroxyvitamin D3 [1a(OH)D3] on mice in the forced swimming test. Intragastric administration of 1.0 mg/kg of 1a(OH)D3 reduced immobility time in the forced swimming test. At all concentrations tested (0.5, 1.0, 2.0 mg/kg), 1a(OH)D3 had no effect on locomotor activity, compared with controls. These results suggest that 1a(OH)D3 may have antidepressant-like activity. Key Words 1a-hydroxyvitamin D3, forced swimming test, glial cell line-derived neurotrophic factor, brain-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Similarly, vitamin D has been linked to depression, and low vitamin D levels have been linked to depressive symptoms [ 7 ]. In line with our findings, previous studies showed that acute [ 35 ], and chronic administration of vitamin D in animals [ 36 ] resulted in a reduction in the immobility time in the forced swim test. Moreover, vitamin D deficiency in mice resulted in depressive symptoms [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, vitamin D has been linked to depression, and low vitamin D levels have been linked to depressive symptoms [ 7 ]. In line with our findings, previous studies showed that acute [ 35 ], and chronic administration of vitamin D in animals [ 36 ] resulted in a reduction in the immobility time in the forced swim test. Moreover, vitamin D deficiency in mice resulted in depressive symptoms [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…5,6) In addition, magnesium ions, which are generated when MgO is dissolved, form chelate complexes with dicumarol, such as warfarin, and quinolone antibacterial agents, such as ciprofloxacin. [7][8][9] These physicochemical interactions are considered to interfere with the efficacy of duloxetine by affecting its absorption, but no previous studies have examined the interactions between duloxetine and MgO.…”
mentioning
confidence: 99%